Type 2 diabetes prediction without labs: a systems-level neural framework for risk and behavioral network reorganization - Kiran, Mahreen; Xie, Ying; Ball, Graham; Anjum, Nasreen; Schutte, Rudolph; Pierscionek, Barbara (Frontiers, 2025)
Background: Prediction models for Type 2 Diabetes Mellitus (T2DM) often rely on biochemical markers such as glycated hemoglobin, fasting glucose, or lipid profiles. While clinically informative, these indicators typically reflect established dysglycemia, limiting their value for early prevention. In contrast, psychosocial stress, sleep disturbance, tobacco use, and dietary quality represent modifiable, non-clinical factors that can be observed long before metabolic abnormalities are clinically detectable. Yet most studies examine these factors in isolation or as additive lifestyle scores, overlooking how their interdependencies reorganize in the preclinical phase. A systems-level approach is therefore needed to capture how disruptions in behavioral coherence signal emerging vulnerability. Methods: This study develops a dual-analytic framework that integrates Cox proportional hazards models with artificial neural network (ANN) coherence analysis. Using longitudinal data from the UK Biobank (n=15,774; follow-up up to 17 years), we identified non-clinical predictors of incident T2DM and examined how behavioral networks reorganize across health states. Predictors were screened through multivariate survival analysis and mapped into ANN-derived influence matrices to quantify stability, direction, and systemic coherence of relationships among diet, sleep, psychosocial states, and demographics. Results: Eighteen significant predictors of T2DM onset were identified. Elevated risk was linked to loneliness, psychiatric consultation, emotional distress, insomnia, irregular sleep, tobacco use, and high intake of processed meat, beef, and refined grains. Protective effects were observed for 7–8 h of sleep, oat and muesli consumption, and fermented dairy. ANN analyses revealed a pronounced breakdown of behavioral coherence in T2DM: foods that stabilized mood in healthy individuals became associated with distress, age and BMI lost their anchoring roles, and emotional states emerged as dominant but erratic drivers of diet. These reversals and destabilizations were consistent across model iterations, suggesting robust signatures of preclinical vulnerability. Conclusion: T2DM risk is better conceptualized as systemic reorganization within behavioral networks rather than the additive effects of isolated factors. By combining survival models with ANN-derived coherence mapping, this study demonstrates that early prediction is possible from modifiable, everyday behaviors without laboratory measures. The framework highlights leverage points for psychologically informed, personalized prevention strategies.
Section: Health Informatics
Keywords: behavioral coherence breakdown; early disease prediction; machine learning; neural network modeling; psychosocial risk factors; survival analysis; Type 2 Diabetes Mellitus (T2DM); 4202 Epidemiology; 42 Health Sciences; Basic Behavioral and Social Science; Machine Learning and Artificial Intelligence; Mental Health; Diabetes; Sleep Research; Social Determinants of Health; Behavioral and Social Science; Obesity; Nutrition; Clinical Research; Brain Disorders; Prevention; 2.3 Psychological, social and economic factors; 3 Good Health and Well Being; 4203 Health services and systems